列车牵引逆变器的转矩控制装置 (2019)
本发明提供种列车牵引逆变器的转矩控制装置。该装置包括：三轴加速度传感器、DSP控制器和牵引逆变器主控单元，DSP控制器分别与三轴加速度传感器、牵引逆变器主控单元连接；三轴加速度传感器，用于测量当前时刻列车的三轴加速度值；DSP控制器，用于根据当前时刻列车的三轴加速度值确定当前时刻列车的倾斜角，并根据从牵引逆变器主控单元中获得的当前时刻列车的载重信息和倾斜角确定当前时刻牵引逆变器的转矩补偿值，并将转矩补偿值发送给牵引逆变器主控单元，以使牵引逆变器主控单元根据转矩补偿值和当前时刻的预设转矩值得到实际转矩值并输出给牵引逆变器，进而实现列车的平稳启动，提高乘客的乘车舒适性。 The invention provides a torque control device of a traction invertor of a train. The torque control device comprises a three-axis acceleration sensor, a DSP (Digital Signal Processing) controller and a traction invertor main control unit, wherein the DSP controller is connected with the three-axis acceleration sensor and the traction invertor main control unit separately; the three-axis acceleration sensor is used for measuring the three-axis acceleration valve of the train at the current time; the DSP controller is used for determining an oblique angle of the train at the current time according to the three-axis acceleration valve of the train of the current time, and determining a torque compensation value of the traction in